1993
DOI: 10.1177/019459989310900510
|View full text |Cite
|
Sign up to set email alerts
|

The role of ktp laser in revision stapedectomy

Abstract: In recent years, the safety and efficacy of revision stapedectomy has come under scrutiny. Experienced surgeons report that the results of such surgery are often worse than the results after primary surgery and that the risks of sensorineural hearing loss, tinnitus, and vertigo are increased. With the addition of laser technology to revision stapes surgery, the procedure to open the neomembrane over the oval window and gain access to the inner ear can now be performed safely. This allows positive identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 14 publications
0
42
1
1
Order By: Relevance
“…McGee et al (1993) reported on 185 KTP laser revision stapedotomy cases, of which 77 involved actual removal of an existing prosthesis. The surgery also involved the creation of a fresh, new fenestra and the placement of a prosthesis.…”
Section: Sensorineural Hearing Lossmentioning
confidence: 99%
“…McGee et al (1993) reported on 185 KTP laser revision stapedotomy cases, of which 77 involved actual removal of an existing prosthesis. The surgery also involved the creation of a fresh, new fenestra and the placement of a prosthesis.…”
Section: Sensorineural Hearing Lossmentioning
confidence: 99%
“…Argon, KTP, and carbon dioxide lasers have all been reported to be very useful in revision stapedectomy (Lesinski and Stein 1989;McGee et al 1993;Palva and Ramsey 1990).…”
Section: Revision Stapedectomymentioning
confidence: 99%
“…At the moment it is widely used in the vaporization of prostatic tumours (11-13) and in otolaryngological surgery of the larynx and epiglottis therapy of papillomatosis. tonsillectomies, naso-farinx tumours and ear-nose small bones operations (14-18). …”
Section: Introductionmentioning
confidence: 99%